A shrinking core model for steam hydration of CaO-based sorbents cycled for CO2 capture - Blamey,J; Fennell,P; Anthony,E; Dugwell,D; Zhao,M; Manovic,V (Chemical Engineering Journal, 2016)
Calcium looping is a developing CO2 capture technology. It is based on the reversiblecarbonation of CaO sorbent, which becomes less reactive upon cycling. One method ofincreasing the reactivity of unreactive sorbent is by hydration in the calcined (CaO) form.Here, sorbent has been subjected to repeated cycles of carbonation and calcination within asmall fluidised bed reactor. Cycle numbers of 0 (i.e., one calcination), 2, 6 and 13 have beenstudied to generate sorbents that have been deactivated to different extents. Subsequently,the sorbent generated was subjected to steam hydration tests within a thermogravimetricanalyser, using hydration temperatures of 473, 573 and 673 K. Sorbents that had beencycled less prior to hydration hydrated rapidly. However, the more cycled sorbents exhibitedbehaviour where the hydration conversion tended towards an asymptotic value, which is likelyto be associated with pore blockage. This asymptotic value tended to be lower at higherhydration temperatures; however, the maximum rate of hydration was found to increase withincreasing hydration temperature. A shrinking core model has been developed and applied to 2the data. It fits data from experiments that did not exhibit extensive pore blockage well, butfits data from experiments that exhibited pore blockage less well